7,8-Dihydroxyflavone Ameliorates Cognitive Impairment by Inhibiting Expression of Tau Pathology in ApoE-Knockout Mice - Tan, Yang; Nie, Shuke; Zhu, Wende; Liu, Fang; Guo, Hailong; Chu, Jiewen; Cao, Xue B.; Jiang, Xingjun; Zhang, Yunjian; Li, Yuzhen (Frontiers in Aging Neuroscience, 2016)
7,8-Dihydroxyflavone (7,8-DHF), a tyrosine kinase B (TrkB) agonist that mimics the neuroprotective properties of brain-derived neurotrophic factor, which can not efficiently deliver into the brain, has been reported to be useful in ameliorating cognitive impairment in many diseases. Researches have indicated that apolipoprotein E-knockout (ApoE-KO) mouse was associated with cognitive alteration via various mechanisms. Our present study investigated the possible mechanisms of cognitive impairment of ApoE-KO mouse fed with western type diet and the protective effects of 7,8-DHF in improving spatial learning and memory in ApoE-KO mouse. 5-weeks-old ApoE-KO mice and C57BL/6 mice were chronically treated with 7,8-DHF (with a dosage of 5mg/kg) or vehicles orally for 25 weeks, and then subjected to Morris water maze at the age of 30 weeks to evaluate the cognitive performances. Afterwards, histology analysis and western blotting were performed. Spatial learning and memory deficits were observed in ApoE-KO mice, which were consistent with higher expression of active-asparaginyl endopeptidase (active-AEP) as well as AEP-derived truncated tauN368 compared with normal group. In addition to that, long-term treatment of 7,8-DHF dramatically ameliorated cognitive decline in ApoE-KO mice, accompanied by the activation in phosphorylated protein kinase B (Akt)/glycogen synthase kinase-3β (GSK-3β) pathway and down-regulated expression of tau S396 and PHF-tau (phosphorylated tau at ser396 and ser404 epitope). These findings suggested that cognitive impairment of ApoE-KO mouse might associate with tau pathology and 7,8-DHF could activate AKT and then phosphorylate its downstream molecule to inhibit expression of abnormal tau, meanwhile, 7,8-DHF could reduce the expression of active-AEP and then inhibit production of truncated tauN368.